Suicide on Death Row. Issue 6 (3rd October 2016) - Tartaro, Christine; Lester, David
Abstract: Despite the level of supervision of inmates on death row, their suicide rate is higher than both the male prison population in the United States and the population of males over the age of 14 in free society. This study presents suicide data for death row inmates from 1978 through 2010. For the years 1978 through 2010, suicide rates on death row were higher than that for the general population of males over the age of 15 and for state prisons for all but 2 years.